Association between Anxiety and Dyspepsia among Outpatients at Atma Jaya Hospital - Heryadi, Samantha Yaffa; Tenggara, Riki; Suryani, Eva; Widjaja, Nelly Tina; Hardi, Nicholas (The Indonesian Society for Digestive Endoscopy, 2024)
Background: Anxiety is a psychological condition characterized by excessive fear and worry that occurs continuously and is difficult to control. Anxiety play a significant role in causing dyspepsia through the Brain-Gut Axis mechanism. Although, there are many cases of anxiety and dyspepsia in Indonesia, there is still a lack of research on the relationship between anxiety and dyspepsia in Indonesia, especially in the clinic. Therefore, this study aimed to determine the relationship between anxiety and dyspepsia among outpatients at Atma Jaya Hospital.Method: This cross-sectional study was conducted on outpatients at Atma Jaya Hospital to investigate the relationship between anxiety and dyspepsia. The demographic and patient characteristic data, including gender, age, highest level of education, and habits, such as eating spicy food, drinking coffee, alcohol consumption, smoking, and NSAID used were collected. The GAD-7 and SF-LDQ questionnaires, which have been validated in Indonesian, were used in this study. Spearman correlation test was used to analyze the data to find the relationship between anxiety and dyspepsia.Results: This study obtained 158 participants. The age range of participants who experienced dyspepsia the most is 19-44 years(77.53%). The majority of those who experienced dyspepsia are female (79.12%). The highest education level of the participants who experienced dyspepsia is a Master’s degree (100%). Participants who consumed spicy food accounted for 61.39% while 54.43% consumed coffee, 6.96% consumed alcohol, 12.66% smoked, and 1.90% used NSAIDs. Additionally, 105 participants (66.46%) experienced both anxiety and dyspepsia. The Spearman correlation test results showed a significant relationship between anxiety and dyspepsia (p-value = 0.000) and a moderate correlation (rs = 0.450). Conclusion: There is a moderate correlation between anxiety and dyspepsia. Keywords: Anxiety, Dyspepsia, GAD-7, Heartburn, SF-LDQ.